New species of Areca, Pinanga, and Licuala (Arecaceae) from Vietnam - Henderson, A.; Ban, N. K.; Thanh, B. V. (Phytotaxa, 2014)
Three new species of palms (Arecaceae) in the genera Areca (A. songthanhensis), Licuala (L. dakrongensis) and Pinanga (P. nuichuensis) from Vietnam are described and illustrated. Comparisons are made and differences with similar species are pointed out.